2013
DOI: 10.1071/cp13149
|View full text |Cite
|
Sign up to set email alerts
|

In vitro ruminal fermentation characteristics and methane production differ in selected key pasture species in Australia

Abstract: Thirteen current and potential pasture species in southern Australia were examined for differences in their nutritive values and in vitro rumen fermentation profiles, including methane production by rumen microbes, to assist in selection of pasture species for mitigation of methane emission from ruminant livestock. Plants were grown in a glasshouse and harvested at 7 and 11 weeks after sowing for in vitro batch fermentation, with nutritive values assessed at 11 weeks of growth. The pasture species tested diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 39 publications
3
28
0
5
Order By: Relevance
“…Consequently, there has been extensive research into technical options for emission-reduction over a period of decades [153]. These include provision of additional dietary oils [154], ionophores and other additives [19] including 3-nitrooxypropanol (3NOP) [155], nitrates [156], tannins and saponins [157], specific shrubs and pasture species with anti-methanogenic properties [154,157], higher digestibility forages and feedstuffs such as red-algae [158], anti-methanogenic vaccines [159] and genetic selection for lower emissions [160]. These options vary in their effectiveness (up to 30% reduction but most reduce emissions by 5% to 10%) and availability, and many of them are impractical or unsuited to extensively grazed livestock systems.…”
Section: Emission Reduction Optionsmentioning
confidence: 99%
“…Consequently, there has been extensive research into technical options for emission-reduction over a period of decades [153]. These include provision of additional dietary oils [154], ionophores and other additives [19] including 3-nitrooxypropanol (3NOP) [155], nitrates [156], tannins and saponins [157], specific shrubs and pasture species with anti-methanogenic properties [154,157], higher digestibility forages and feedstuffs such as red-algae [158], anti-methanogenic vaccines [159] and genetic selection for lower emissions [160]. These options vary in their effectiveness (up to 30% reduction but most reduce emissions by 5% to 10%) and availability, and many of them are impractical or unsuited to extensively grazed livestock systems.…”
Section: Emission Reduction Optionsmentioning
confidence: 99%
“…Evidentemente, estos resultados indican que el principal mecanismo por el cual se encontraron menores valores de metano con esta planta, es porque se afectó la MSD (Bodas et al, 2012;Durmic et al, 2010), sin embargo, no se observaron reducciones en las proporciones de los principales AGV (acetato, butirato y propionato) y tampoco en los AGVT. Efectos similares se han encontrado en las plantas Biserrula pelecinus L. y Eremophila glabra (Banik et al, 2013;Li, 2013).…”
Section: Discussionunclassified
“…A pesar de que la inclusión del 75 % de la especie E. schomburgkii disminuyó la MSD y la producción de gas, la fermentación del sustrato se mantuvo en niveles adecuados como para que no se afectara la concentración de los AGVT. La menor producción de gas se puede atribuir a que se redujo la proporción de metano presente en el gas (Banik et al, 2013), lo que sugiere un efecto adverso sobre la metanogénesis. Aparentemente, el efecto de los compuestos secundarios presentes en la especie E. schomburgkii afectan negativamente a las poblaciones de microorganismos ruminales en general, siendo este efecto menor en los microorganismos celulolíticos y posiblemente mayor sobre las poblaciones de bacterias metanogénicas.…”
Section: Discussionunclassified
“…Several parameters of rumen fermentation system can be used to determine the quality of ruminant feed such as gas production, IVOMD and CH 4 concentration. Banik et al (2013) identified that CH 4 production had a positive correlation with some fermentation parameters such as gas pressure and acetate : propionate ratio. The fermentation characteristics of gas production, IVOMD and CH 4 concentration are shown in Table 2.…”
Section: Rumen Fermentation and Methane Mitigationmentioning
confidence: 99%